Studi Pemberian Kalsium untuk Mengatasi Getah Kuning pada Buah Manggis (Garcinia mangostana L.) - , Dorly; Indah Wulandari; Roedhy Poerwanto; Darda Efendi; Soekisman Tjitrosemito (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
Gamboge is the main problem in mangosteen agribusiness because it is one of the major factors lowering fruit quality. Calcium is one of the important elements that strengthening cell wall; it is which was binding with the pectin as a middle lamella component. The objectives of the research were to study the effect of calcium application on the presence of gamboge spots, physical, and chemical properties of mangosteen fruit. Trial was conducted in a randomized complete block design with three replications in two consecutive years. The calcium source was dolomite, applied in four different dosages, i.e. 0, 18, 24, and 34 ton ha-1 for the fi rst year and 0, 12.5, 15, and 17.5 ton ha-1 for the second year. The results showed that calcium application raised soil pH and calcium content of the soil, exocarp and mangosteen leaves. Dolomite applications using 18 and 24 ton ha-1 in the fi rst year and 17.5 ton ha-1 in the second year were effective to reduce gamboge spots on the outer part of fruit, however they were not effective to reduce gamboge in aril. Dolomite applications did not increase transversal diameter, fruit weight, total soluble solids, total titratable acids, and ratio of total soluble solids with total titratable acids of the fruits.